PENGARUH TINGKAT PENDIDIKAN, PENGANGGURAN DAN KEMISKINAN TERHADAP KRIMINALITAS DI PROVINSI ACEH - Meutia, Rachmi; Amri, Khairul; Indah (Faculty of Islamic Economics and Business at Universitas Islam Negeri Ar-Raniry in Banda Aceh, Indonesia, 2024)
The act of criminality is a violation of the relevant laws and norms, and it is strongly opposed by society. The objective of this study is to investigate the effect of education level, unemployment, and poverty on criminality in Aceh. This study employs a quantitative approach with panel data. The result shows that the fixed-effect model is the optimal one. The results of this study indicate that the level of education and poverty has a negative and significant effect on crime in Aceh Province, while unemployment has a positive and insignificant effect on crime in Aceh Province. This study highlights how crucial it is for Aceh Province to implement multifaceted policies and strategic measures to combat criminal activity by raising the standard of education in Aceh, which is focused on job skills and community-based economic empowerment to lower poverty.